2014
DOI: 10.1371/journal.pone.0097414
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic In Vitro and In Vivo Antitumor Effect of Combination Therapy with Salinomycin and 5-Fluorouracil against Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the few cancers in which a continuous increase in incidence has been observed over several years. Drug resistance is a major problem in the treatment of HCC. In the present study, we used salinomycin (Sal) and 5-fluorouracil (5-FU) combination therapy on HCC cell lines Huh7, LM3 and SMMC-7721 and nude mice subcutaneously tumor model to study whether Sal could increase the sensitivity of hepatoma cells to the traditional chemotherapeutic agent such as 5-FU. The combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 42 publications
(38 reference statements)
4
32
1
Order By: Relevance
“…This is accompanied by inhibition of tumor cell migration and invasion. Interestingly, in contrast to other observations before, an additive synergistic effect of Sal and 5-FU in vitro was not observed [2628]. …”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…This is accompanied by inhibition of tumor cell migration and invasion. Interestingly, in contrast to other observations before, an additive synergistic effect of Sal and 5-FU in vitro was not observed [2628]. …”
Section: Discussioncontrasting
confidence: 92%
“…Given that CRC liver metastasis are the leading cause for CRC-related death [4] this observation promises an important clinical impact. The effectiveness of Sal in vivo has been described before predominantly in subcutaneous tumor models [1, 7, 17, 26, 2931]. Our data demonstrate the effectiveness of Sal in clinical relevant CRC models for the first time in a convincing extent.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Xiaowei Recently, emerging studies of breast cancer 5 , ovarian cancer 6 , hepatocellular carcinoma 7 and lung adenocarcinoma 8 have demonstrated that drug-resistant cancer cells display features of epithelial-mesenchymal transition (EMT). It is well-known that EMT is an essential physiological process in which epithelial cells change into mesenchymal cells through a specific signaling pathway.…”
Section: Salvianolic Acid a Reverses The Paclitaxel Resistance And Inmentioning
confidence: 99%
“…Persistent activation of Notch signaling may lead to oncogenesis depending on modifier factors, including the inflammatory environment or the presence of other carcinogenic conditions that may cause HCC or CCA (88). A Notch signature has been reported in a subset of HCC patients and an overexpression of Notch receptors has been reported in human CCAs, which is fundamentally required for the development of targeted therapies (89).…”
Section: Notch-based Therapeutic Strategies In Liver Cancermentioning
confidence: 99%